Prostate MRI characteristics in patients with inflammatory bowel disease. Issue 135 (February 2021) - Takahashi, Hiroaki; Froemming, Adam T.; Bruining, David H.; Karnes, R. Jeffrey; Jimenez, Rafael E.; Takahashi, Naoki
Abstract: Purpose: Previous studies have indicated an increased risk of prostate carcinoma (PCa) associated with inflammatory bowel disease (IBD). Prostate MRI of IBD patients could be expected to show a mixture of inflammation as well as higher than normal rates of PCa, which could impact interpretation and MRI performance. The purpose of this study is to evaluate the characteristics of prostate MRI in patients with IBD. Methods: 3140 patients with prostate MRI were evaluated. Coexisting IBD, PI-RADS score, and pathological results of prostate lesions (clinically significant PCa [csPCa]: Gleason score [GS] 7+, Non-csPCa: benign or GS 6) were assessed. The distribution of PI-RADS scoring and pathological result was assessed by chi-square test. Results: 71 patients had IBD (IBD group), whereas the remaining 3069 patients did not (Non-IBD group). The proportion of abnormal MRI (PI-RADS 3, 4 or 5) was 51 % (36/71) in IBD group and 47 % (1436/3069) in Non-IBD groups (p = 0.513). Total of 1285 patients underwent biopsy or prostatectomy. The proportion of csPCa at pathology was 35 % (12/34) in IBD group and 56 % (699/1251) in non-IBD groups (p = 0.017). The positive predictive value of abnormal MRI for csPCa was significantly lower in IBD group (39 %, 19/31) compared to Non-IBD group (63 %, 657/1047) (p = 0.007). Conclusion: The proportion of csPCa at pathology and positive predictive value of abnormal MR for csPCa were lower in patients with IBD group compared to Non-IBD group.